Bulimia nervosa‐nonpurging subtype: Closer to the bulimia nervosa‐purging subtype or to binge eating disorder?. Issue 3 (26th November 2013) - Jordan, Jennifer; McIntosh, Virginia V.W.; Carter, Janet D.; Rowe, Sarah; Taylor, Kathryn; Frampton, Christopher M.A.; McKenzie, Janice M.; Latner, Janet; Joyce, Peter R.
Abstract Objective DSM‐5 has dropped subtyping of bulimia nervosa (BN), opting to continue inclusion of the somewhat contentious diagnosis of BN‐nonpurging subtype (BN‐NP) within a broad BN category. Some contend however that BN‐NP is more like binge eating disorder (BED) than BN‐P. This study examines clinical characteristics, eating disorder symptomatology, and Axis I comorbidity in BN‐NP, BN‐P, and BED groups to establish whether BN‐NP more closely resembles BN‐P or BED. Method Women with BN‐P (n = 29), BN‐NP (n = 29), and BED (n = 54) were assessed at baseline in an outpatient psychotherapy trial for those with binge eating. Measures included the Structured Clinical Interviews for DSM‐IV, Eating Disorder Examination, and Eating Disorder Inventory‐2. Results The BN‐NP subtype had BMIs between those with BN‐P and BED. Both BN subtypes had higher Restraint and Drive for Thinness scores than BED. Body Dissatisfaction was highest in BN‐NP and predicted BN‐NP compared to BN‐P. Higher Restraint and lower BMI predicted BN‐NP relative to BED. BN‐NP resembled BED with higher lifetime BMIs; and weight‐loss clinic than eating disorder clinic attendances relative to the BN‐P subtype. Psychiatric comorbidity was comparable except for higher lifetime cannabis use disorder in the BN‐NP than BN‐P subtype Discussion These results suggest that BN‐NP sits between BN‐P and BED however the high distress driving inappropriate compensatory behaviors in BN‐P requires specialist eating disorder treatment. These results support retaining the BN‐NP group within the BN category. Further research is needed to determine whether there are meaningful differences in outcome over follow‐up. © 2013 Wiley Periodicals, Inc. (Int J Eat Disord 2014; 47:231–238)